Coercive And Voluntary Assimilation: A Comparison Of Chinese Assimilation Under The New Order And Assimilation With The Simalungun Ahap (Journal of Namibian Studies : History Politics Culture, 2024)
The various ethnicities in a certain area have implications for the emergence of a new order to determine the new composition of society. The formulation of new values takes place over a long period of time with a dynamic form of negotiation between ethnicities in it. The acceptance of all parties to the new order can be done through forced and voluntary assimilation. Coercive assimilation is done with dominant power through policy, obligation and lack of choice. In the Indonesian context, forced assimilation is still fresh in memory with the fusion of Chinese identity into Indonesian through a series of imposed policies. Conceptually, assimilation brings together differences to merge with the larger society and become a new, harmonized form. In reality, this forced assimilation still leaves a form of ethnic Chinese inequality until now. This pessimistic form of assimilation implies the impossibility of voluntary assimilation in Indonesia. However, in a small area of North Sumatra, Simalungun district, voluntary assimilation has been going on for a long time and is able to unite the differences that exist by all units of difference. One of the drivers of assimilation is the use of the Simalungun ahap which is able to bind and make Simalungun a common good. This optimism gives hope to Indonesia that assimilation can be something genuine to unite the many tribes, religions and races that exist.